Comparison of capabilities of the Unity environment and LibGDX in terms of computer game development - Kosidło, Piotr; Kowalczyk, Karol; Badurowicz, Marcin (Journal of Computer Sciences Institute, 2021)
As part of the work on the article, two 2D games were created – one based on the Unity environment and the other based on LibGDX. Main focus in the work was to compare the performance of both games. For this purpose, research was carried out to determine which game has a better impact on the usage of CPU and RAM resources. Attention was also paid to community support for both tools and the programmer’s comfort during the work in both of these tools. The results of the performance studies suggest that LibGDX may be a better choice for creating small projects where performance is a priority. However, the support of the community and the comfort of working with the environment and the lack of need to use external programs speak in favor of Unity.